PENGGUNAAN ARANG AKTIF, ARANG TONGKOL JAGUNG, PGPR DAN CAIRAN RUMEN SAPI PADA PROSES PRA PENGOMPOSAN KERTAS BEKAS BERTINTA - Rahmawati, Annisa; Kurniahu, Hesti; Sriwulan, Sriwulan (INSTITUT AGAMA ISLAM NEGERI AMBON, 2021)
The process of composting inked waste paper can be done because inked waste paper contains organic material in the form of cellulose, hemicellulose, lignin and ash compounds. But unlike other organic materials inked used paper has undergone various chemical processes in its manufacture so it needs to be done soaking treatment in advance to reduce the content of various chemicals. In this case inked scrap paper is soaked with distilled water added with activated charcoal, corn cobs charcoal, PGPR and rumen liquid. The PGPR was then added to a phosphate buffer of pH 7 and incubated for 7 days at room temperature without exposure to sunlight. Rumen fluid is taken at the Jenu Slaughterhouse in Tuban Regency, this liquid is taken directly after the cow is slaughtered and put into a flask then phosphate buffer pH 7 is added and incubated for 7 days at room temperature and not exposed to sunlight. Provision of activated charcoal, corn cobs charcoal and PGPR can be done in the process of precomposting inked waste paper with a cow rumen liquid starter without causing pH and temperature fluctuations. Keywords: Activated Charcoal, Corncob Charcoal, Pgpr, Rumen Liquid, Waste Paper